Personal Branding of Anies Baswedan Through Facebook And Twitter Account: Study Of Image Grid Analysis in Banjarmasin Society Aged 17 – 24 Years - RAMADHAN FEBRIAN ANSHARI; SETYASTUTI YUANITA; MAULINA NOVARIA (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2016)
This research aimed was the grid of personal branding image of Anies Baswedanthrough Facebook and Twitter account on Banjarmasin society. This researchused quantitative approach with descriptive type. The population was Banjarmasin society aged 17-24 years old. Sample that taken was 399 people, sample retrieval techniques used cluster random sampling. The method of data collection used questionnaire and observation, while the method of data analysis used image analysis grid by Kotler with the degree of trust was 95%. The results of the research, personal branding image of anies baswedan on familiarity scale is74,44% or 297 respondents from 399 respondent of total samples, categorizedon less know about Anies Baswedan. That means only 25,56% or 102 respondents who know him. Based on favorability scale there were 76,25% or 77 respondents from 102 respondents who know Anis Baswedan, categorized him asa good image of personal branding. Based on grid analysis model Anis Baswedan’s Personal Branding are less known and good image. That means personal branding image of anies baswedan was located on grid B, that was the assessment of respondents about Anies Baswedan was he does not well known but he has a good image.